A MANAGEMENT OF A CASE WITH SPONDYLOLISTHESIS & DISC PROLAPSE THROUGH CLINICAL REASONING PROCESS: case report - disha, fabiha alam (Jour Med Resh and Health Sci, 2019)
Clinical reasoning is the thinking and decision making process in professional practice of a health professional. In our routine and daily practice, each and every case constitutes different types of presentations related to clinician’s knowledge, cognitive skill, decision making skill and clinical reasoning skill. Low back pain with radicular symptom among middle age female specially housewife considered as one of the most common musculoskeletal features in now a day. Some of the cases extend to disabling condition that limits activity, performance and lead to disability. Clinician compresses inductive and deductive ways of clinical reasoning to solve this condition. Sometimes, all the features can’t be solved in a single reasoning procedure based on knowledge and cognition. With the induction of unfamiliar symptoms clinician looks for the cues and decides with the formation and evaluation of hypothesis. In this case, the case of low back pain with radicular symptom has been treated with both inductive and deductive strategy of clinical reasoning skill. Also, the client’s desire, limitation, disabilities and occupational performance has been considered as a parameter to improvement. Within few weeks with an efficient and scientific way of clinical reasoning skill, the case had a satisfactory improvement in his functioning, disability and health status.